The tap dance mystery - Pearson, Susan; Fiammenghi, Gioia; Pearson, Susan; Fiammenghi, Gioia (New York: Simon and Schuster Books for Young Readers, 1990)
Amidst the school's preparation for parents nights, Eagle-Eye Ernie solves the mystery of a pair of missing tap shoes.
Dance or Quit--Bananas and Tap Shoes--Ms. Finney's Woodpeckers--Shuffle off to Buffalo--The Marcie Move--A job for Eagle Eye Ernie--Eagle-Eye Ernie Goes to Work--The Surprise at Twin Tress-- With or without Magic--The Surprise Solution-- The Night Big Pearson, Susan
English